2013
DOI: 10.1089/ten.tea.2012.0520
|View full text |Cite
|
Sign up to set email alerts
|

Titanium-Enriched Hydroxyapatite–Gelatin Scaffolds with Osteogenically Differentiated Progenitor Cell Aggregates for Calvaria Bone Regeneration

Abstract: Adequate bony support is the key to re-establish both function and esthetics in the craniofacial region. Autologous bone grafting has been the gold standard for regeneration of problematic large bone defects. However, poor graft availability and donor-site complications have led to alternative bone tissue-engineering approaches combining osteoinductive biomaterials and three-dimensional cell aggregates in scaffolds or constructs. The goal of the present study was to generate novel cell aggregate-loaded macropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…However, recent advances in 3-dimensional printing techniques, such as robocasting, have enabled scaffold manufacture with highly controlled pore architecture and morphology (Ricci et al, 2012). A study from the National Institute of Dental and Craniofacial Research demonstrated that the combination of titanium dioxide with a hydroxyapatite-gelatin macroporous scaffold had comparable strength relative to natural calvarial bone in a study of rat critical-sized calvarial defects (Ferreira et al, 2013).…”
Section: Natural and Synthetic Polymersmentioning
confidence: 99%
“…However, recent advances in 3-dimensional printing techniques, such as robocasting, have enabled scaffold manufacture with highly controlled pore architecture and morphology (Ricci et al, 2012). A study from the National Institute of Dental and Craniofacial Research demonstrated that the combination of titanium dioxide with a hydroxyapatite-gelatin macroporous scaffold had comparable strength relative to natural calvarial bone in a study of rat critical-sized calvarial defects (Ferreira et al, 2013).…”
Section: Natural and Synthetic Polymersmentioning
confidence: 99%
“…All animal care and experimental procedures were approved by the University of North Carolina at Chapel Hill Institutional Animal Care and Use Committee (IACUC09-270.0) in compliance with the NIH Guide for Care and Use of Laboratory Animals. All surgical procedures were followed the same protocol as previously described [23]. Briefly, an 8 mm critical-sized defect was created on the calvarium.…”
Section: Regeneration Of Rat Calvarium Defectmentioning
confidence: 99%
“…After 12 weeks postoperatively, each calvarium was harvested, sectioned (nondecalcified), and stained with Steven's Blue and counterstained with Van Gieson. The process of the non-decalcified section was well described in previous study [23]. The medial sagittal sections were chosen and acquired color images using a light microscope (Nikon Eclipse Ti-U, Nikon, Japan) mounted with an Olympus DP12 camera.…”
Section: Regeneration Of Rat Calvarium Defectmentioning
confidence: 99%
“…1 A variety of bone grafting or substitutes [2][3][4][5] have been placed in these defects in order to facilitate and/or promote bone healing. However, the problems associated with bone healing followed bone reconstruction may be associated more with systemic skeletal disorders.…”
Section: Introductionmentioning
confidence: 99%